Impact of GeneXpert MTB/RIF® on treatment initiation and outcomes of RIF-resistant and RIF-susceptible TB patients in Vladimir TB dispensary, Russia - Ershova, Julia V.; Volchenkov, Grigory V.; Somova, Tatiana R.; Kuznetsova, Tatiana A.; Kaunetis, Natalia V.; Kaminski, Dorothy; Demikhova, Olga V.; Chernousova, Larisa N.; Vasilyeva, Irina A.; Kerr, Eleanor M.; Cegielski, J. Peter; Kurbatova, Ekaterina V. (BMC infectious diseases, 2020)
Background The main advantage of GeneXpert MTB/RIF ® (Xpert) molecular diagnostic technology is the rapid detection of M .tuberculosis DNA and mutations associated with rifampicin (RIF) resistance for timely initiation of appropriate treatment and, consequently, preventing further transmission of the disease. We assessed time to treatment initiation and treatment outcomes of RIF-resistant and RIF-susceptible TB patients diagnosed and treated in Vladimir TB Dispensary, Russia in 2012, before and after implementation of GeneXpert MTB/RIF® diagnostic technology. Methods All adult patients suspected of having TB during February–December 2012 underwent a clinical examination, chest x-ray, microscopy, culture, and phenotypic drug susceptibility testing (DST). Starting August 2012 Xpert diagnostic technology became available in the facility. We used logistic regression to compare treatment outcomes in pre-Xpert and post-Xpert periods. Kaplan-Meier curves and log-rank test were used to compare the time to treatment initiation between the groups. Results Of 402 patients screened for TB during February–December 2012, 338 were diagnosed with TB (280 RIF-susceptible, 58 RIF-resistant). RIF-resistant patients in the post-Xpert group started treatment with second-line drugs (SLD) earlier than those in pre-Xpert group (median 11 vs. 37 days, Log-rank p = 0.02). The hazard ratio for time to SLD treatment initiation was significantly higher in post-Xpert group (HR:2.06; 95%CI:1.09,3.89) compared to pre-Xpert group. Among the 53/58 RIF-resistant TB patients with available treatment outcome, 28 (53%) had successful outcomes (cured/completed treatment) including 15/26 (58%) in post-Xpert group versus 13/27 (48%) in pre-Xpert group. The observed difference, however, was not statistically significant (OR:0.69; 95%CI:0.23,2.06). Among RIF-susceptible TB cases time to treatment initiation was not significantly different between the groups (2 vs. 3 days, Log-rank p = 0.73). Of 252/280 RIF-susceptible TB cases with treatment outcome, 199 (79%) cases had successful outcome including 94/114 (82%) in post-Xpert group versus 105/138 (76%) in pre-Xpert group (OR:0.68; 95%CI:0.36,1.26). Conclusion We observed that availability of Xpert for initial diagnosis significantly reduced the time to SLD treatment for RIF-resistant patients in the Vladimir TB Dispensary. Although implementation of rapid diagnostics did not improve treatment outcomes, early diagnosis of MDR-TB is important for selection of appropriate treatment regimen and prevention of transmission of drug-resistant strains of TB.